The Advanced Oxidation of Congo Red and Nigrosine Using Dimethyl Dioxirane as an Oxidizing Agent - S. Vinotha; A. Leema Rose (Progress in Chemical Science Research Vol. 9, 2023)
This work describes the advanced oxidation of Congo red (CR) and nigrosine (NI) using dimethyl dioxirane as an oxidizing agent. Nigrosine dye is a mixture of fake dark colors (CI 50415, Solvent dark 5) made by warming a mixture of aniline, nitrobenzene, and aniline hydrochloride in a copper or iron-like atmosphere. The effects of a number of factors, including the pH, initial dye concentration, and oxidizing agent concentration, have been studied. The dimethyl dioxirane was used to investigate the degradation of CR and NI dyes at room temperature. The effects of pH, an oxidizing agent, and the initial dye concentration were studied with respect to the degradation efficiency of CR and NI. Using UV-visible spectroscopy, the absorbance of CR and NI dyes was determined both before and after degradation. Utilizing FT-IR spectroscopy, it was possible to compare the functional group that existed in the dyes before and after degradation. This work could also be expanded to include the decolorization of industrial effluents that contain dyes as significant contaminants.